Identification and Expression Profiles of 14 Odorant-Binding Protein Genes From Pieris rapae (Lepidoptera: Pieridae). Issue 5 (5th September 2020) - Li, Mao-Ye; Jiang, Xiu-Yun; Qi, Yu-Zhe; Huang, Yuan-Jie; Li, Shi-Guang; Liu, Su
Abstract: The small white butterfly, Pieris rapae (L.), is an important insect pest of Brassica crops. This species utilize olfactory cues to find their hosts and mates. However, the molecular mechanism underlying the olfactory perception in this species remains unclear. Here, we identified 14 odorant-binding proteins (OBP) genes—essential for insect olfaction—in P. rapae by exploring a previously published transcriptome dataset. Proteins encoded by all of these genes contain N-terminal signal peptides and six positionally conserved cysteine residues, which are characteristic of insect OBPs. These OBPs displayed high amino acid identity with their respective orthologs in other lepidopterans, and several conserved motifs were identified within these OBPs. Phylogenetic analysis showed that these OBPs were well segregated from each other and clustered into different branches. PrapOBP1 and PrapOBP2 were clustered into the 'general odorant-binding protein' clade, and PrapOBP3 and PrapOBP4 fall into the 'pheromone-binding protein' clade. The 14 OBP genes were located on seven genomic scaffolds. Of these, PrapOBP1, 2, 3, and 4 were located on scaffold332, whereas PrapOBP5, 6, 7, 8, and 9 were located on scaffold116. Ten of the 14 genes had antenna-biased expression. Of these, PrapOBP1, 2, 4, and 13 were enriched in male antennae, whereas PrapOBP7 and PrapOBP10 were female-biased. Our findings suggest that these OBPs may be involved in olfactory communication. To the best of our knowledge, this is the first report on the identification and characterization of OBP s in P. rapae, and our findings provide a solid foundation for studying the functions of these genes.